2021
DOI: 10.17161/eurojecol.v7i1.14749
|View full text |Cite
|
Sign up to set email alerts
|

Regeneration indicators of Detarium microcarpum Guill. & Perl. in the Mbe plain of the Adamawa, Cameroon

Abstract: Background In Africa, the Detarium microcarpum Guill. & Perr. species is extremely important culturally, ecologically and socio-economically. This importance has led to its over-exploitation leading to an in situ rarity of its individuals. As a consequence, a conservation alert is increasingly reported across the continent due to the risk of extinction of this multipurpose plant. Unfortunately, indicators of regeneration and conservation guidelines for this species have been not developped yet. The objecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 24 publications
0
6
0
Order By: Relevance
“…In Nigeria, this species is found in the Sudano-Guinean savanna area of the country. D. microcarpum is one of the prominent elements of the local population's socioeconomic life (Lamy et al2021), and this species is highly appreciated by local communities for its food, medicinal and wood-fuel uses (Gaisberger et al 2017, Agbo et al 2019., Lamy, 2021., Houénon et al2022. The stems of D. microcarpum have been reported to be fully used in the production of wood charcoal in Benin, while in Burkina Faso, D. microcarpum is regarded as one of the top ten woody food species in the country (Houénon et al 2022).…”
Section: Common Name: Sweet Dattockmentioning
confidence: 99%
See 1 more Smart Citation
“…In Nigeria, this species is found in the Sudano-Guinean savanna area of the country. D. microcarpum is one of the prominent elements of the local population's socioeconomic life (Lamy et al2021), and this species is highly appreciated by local communities for its food, medicinal and wood-fuel uses (Gaisberger et al 2017, Agbo et al 2019., Lamy, 2021., Houénon et al2022. The stems of D. microcarpum have been reported to be fully used in the production of wood charcoal in Benin, while in Burkina Faso, D. microcarpum is regarded as one of the top ten woody food species in the country (Houénon et al 2022).…”
Section: Common Name: Sweet Dattockmentioning
confidence: 99%
“…Due to its economic value, the Federal Government of Nigeria has established a tree breeding centre for Shea species in Bida Niger State (Ugese et al 2010;Mohammed et al 2017;Koloche et al 2016 and2021). Even farmers in this region have attempted to domesticate this species as an agroforestry tree.…”
Section: Family: Sapotaceaementioning
confidence: 99%
“…are among the most exploited species in Burkina Faso (Bationo et al, 2001), Benin (Agbo et al, 2019) and Mali (Kouyaté, 2005). These species face vulnerabilities in their occurrence areas, yet their conservation status remains unclassified by the International Union for the Conservation of Nature (IUCN) (Lamy Lamy et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, much research effort has focused on the socioeconomic contributions (Kouyaté et al, 2002; Florence et al, 2014) and regeneration concerns (Agbo et al, 2019; Bationo et al, 2001; Lamy Lamy et al, 2021; Ricez, 2008) of D. microcarpum and D. senegalense . While several studies have shown the importance of Detarium species in food and economic sectors through the exploitation of NTFPs, less attention has been given to local perceptions of the threats to these species.…”
Section: Introductionmentioning
confidence: 99%
“…In Nigeria, this species is found in the Sudano-Guinean savanna area of the country. D. microcarpum is one of the prominent elements of the local population's socioeconomic life(Lamy et al, 2021), and the species is highly appreciated by the local communities for its Due to the adverse effects of climate change which is affecting the natural regeneration of many species in the wild, assisted regeneration is suggested for populations in areas where suitable habitats under favorable environmental conditions(Gaisberger et al, 2017).Diospyros mespiliformis is an evergreen forest and savanna tree up to 25 m high in the savanna, and up to 45 m in forests and usually has a dense rounded, and buttressed stem(Hutchison and Dalziel 1927-1954, Burkhil, 2004). The bark is grey-black or black, smooth in young trees rough with small regular scales in older The estimated extent of occurrence is 4800 km 2 and the estimated area of occupancy is 100 km 2 .…”
mentioning
confidence: 99%